Implementation of Batik Wastewater Management Policy: A Case Study of Pekalongan City - Eka Fadhila; Yuswarni Yuswarni; Achmad Firdaus; Alexsander Yandra; Arizal Arizal (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aims to review the implementation of batik waste management policies in Pekalongan City, this is because Pekalongan is the largest batik producing area in Indonesia with an average production of over sixty percent of the total national production capacity which is dominated by the small-scale batik industry or household industry, and this has caused pollution to the environment, this research uses a qualitative descriptive method with a field study approach compared to literature review or literature study and the results found that the environment, The number of Wastewater Treatment Plants (IPAL) that are still being built is small and not proportional to the amount of waste produced per cubic meter and day and the implementation of policy implementation which does not produce maximum output in overcoming batik wastewater in Pekalongan City because the target of building the number of Wastewater Treatment Plants in Pekalongan City has not been built one hundred percent at this time based on established policies and should be able to accommodate all wastewater from the remaining batik production in Pekalongan City.